New Perspectives in the Management of Diabetic Macular Edema - Siddiqui, M. A. Rehman (Pakistan Journal of Ophthalmology, 2014)
The prevalence of diabetes is increasing worldwide. With urbanization in the developing countries, and increasingly sedentary lifestyle, the incidence of diabetes is reaching an epidemic, particularly among the young. Prevalence of diabetes is estimated to double by 2025 in Pakistan to a staggering 11.6 million people. Pakistan will become the 4th most populous country in terms of the number of diabetics.1 Rising prevalence means the burden of visual loss is likely to increase many folds. To identify sight-threatening retinopathy, systematic screening is recommended. Unfortunately, there is no effective screening programme for diabetic retinopathy in Pakistan. The two most common causes of visual loss in diabetes are proliferative diabetic retinopathy and diabetic macular edema (DME). DME is the commonest cause of visual loss among the working age group.